A cut-and-paste strategy towards liquid crystal elastomers with complex shape morphing. Issue 30 (24th July 2018) - Chen, Ling; Wang, Meng; Guo, Ling-Xiang; Lin, Bao-Ping; Yang, Hong
Abstract : In this work, monodomain liquid crystal elastomer films with exchangeable disulfide crosslinkers are cut into pieces and pasted together through dynamic disulfide exchange to form versatile shaped soft actuator materials. Abstract : Nowadays, with the rapid progress in soft robotics and aerospace technology, novel soft actuator materials with reversible and complex shape morphing capabilities, such as helical curling, buckling, accordion-like folding, self-oscillating, waving and other three-dimensional motion modes, are highly desirable. In this manuscript, we report a new cut-and-paste method to construct liquid crystal elastomer actuators with complex shape morphing by combining dynamic covalent chemistry with the traditional surface-treated liquid crystal cell preparation strategy. In brief, we synthesize monodomain liquid crystal elastomer films with exchangeable disulfide crosslinkers through in situ photopolymerization in anti-parallel surface-rubbed cells, cut the obtained uniaxial-aligned liquid crystal elastomer films into pieces and paste them together via dynamic disulfide exchange to form versatile shaped soft actuator materials.